2022
DOI: 10.3390/ijerph19169904
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Dry Needling and Acupuncture in Patients with Fibromyalgia: A Systematic Review and Meta-Analysis

Abstract: Fibromyalgia (FM) is a syndrome that involves chronic pain, fatigue, sleep disturbance and impaired quality of life and daily functioning. In addition to medical and psychological therapies, other therapies including acupuncture and dry needling aim to reduce pain and disability in patients with FM. The aim of this study was to investigate the efficacy of dry needling and acupuncture in patients with FM regarding pain, function and disability in both the short and the long term. MEDLINE, PubMed, SCOPUS and Web… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 64 publications
1
4
0
Order By: Relevance
“…The results demonstrated that both interventions led to significant improvements in various clinical outcomes, with dry needling showing superior efficacy compared to stretching. These findings align with previous studies that have reported the benefits of non-pharmacological treatments for fibromyalgia (17) The significant reduction in FIQ scores observed in both groups indicates that both dry needling and stretching can effectively alleviate the symptoms of fibromyalgia. However, the more substantial improvements seen in the dry-needling group suggest that this technique might be more effective in targeting specific pain points and reducing associated symptoms.…”
Section: Discussionsupporting
confidence: 91%
“…The results demonstrated that both interventions led to significant improvements in various clinical outcomes, with dry needling showing superior efficacy compared to stretching. These findings align with previous studies that have reported the benefits of non-pharmacological treatments for fibromyalgia (17) The significant reduction in FIQ scores observed in both groups indicates that both dry needling and stretching can effectively alleviate the symptoms of fibromyalgia. However, the more substantial improvements seen in the dry-needling group suggest that this technique might be more effective in targeting specific pain points and reducing associated symptoms.…”
Section: Discussionsupporting
confidence: 91%
“…However, this effect was not detected in the Mental Component Summary (MCS). Previous studies have recommended combining vestibular rehabilitation with other therapeutic strategies, such as education in pain neuroscience or vertigo [70][71][72], relaxation techniques [72] or acupuncture [73], to more successfully address psychological aspects such as anxiety, kinesophobia or catastrophism, and the realization of physical exercise to contribute to the improvement of vertiginous symptomatology and provide well-being [18,74]. For future lines of work, it would be interesting to include a combined care of VR, therapeutic education and physical exercise to seek a complementarity of the different therapies and cover the wide range of symptoms that characterize FMS.…”
Section: Discussionmentioning
confidence: 99%
“…Among these therapies, acupuncture is widely known as one of the common forms to alleviate pain and improve sleep ( 87 , 88 ). For example, acupuncture treatment can reduce pain pressure thresholds and improve sleep disturbances in patients with fibromyalgia ( 89 ). A systematic review and meta-analysis has also shown that acupuncture can relieve pain and improve sleep quality in patients with CP-related insomnia ( 90 ).…”
Section: Clinical Research On the Relationship Between Chronic Pain A...mentioning
confidence: 99%
“…Althogh not recommended by current guidelines, many alternative and complementary therapies are popular worldwide and have been increasingly studied to treat CP and sleep disorders, including music therapy, aromatherapy, massage, and acupuncture (85,86). Among these therapies, acupuncture is widely known as one of the common forms to alleviate pain and improve sleep (87,88). For example, acupuncture treatment can reduce pain pressure thresholds and improve sleep disturbances in patients with fibromyalgia (89).…”
Section: Complementary and Alternative Approachesmentioning
confidence: 99%